Pengembangan Media Ensiklopedia Bentuk dan Fungsi Tumbuhan Melatihkan Berpikir Kritis Siswa Sekolah Dasar - Yeny Erawati; Raharjo Raharjo; Utiya Azizah (Jurnal Bidang Pendidikan Dasar, 2020)
Abstract: Encyclopedia media development research has a goal that is worth practicing the critical thinking of fourth grade students in terms of plant form and function in terms of validity, practicality, effectiveness. This type of quantitative research (R&D) model is Borg and Gall. Data collection techniques: observation, questionnaire, and test. Data analysis techniques: validity and reliability, student activities, lesson plans and critical thinking tests. The results of the Encyclopedia media validator are valid for use, tested at SDN MOJO VI / 225 with One Group Pretest-Postest Design. The results of Encyclopedia media validation> 96% valid, RPP implementation> 94% performed well with the Discovery Learning model, the effectiveness of the N-Gain critical thinking test 0.75 (high), positive response 97%. Conclusion Media Encyclopedia of Plant Form and Function is appropriate to be used to train Critical thinking. Abstrak: Penelitian pengembangan media Ensiklopedia memiliki tujuan yang layak melatihkan berpikir kritis siswa kelas IV materi bentuk dan fungsi tumbuhan ditinjau kevalidan, kepraktisan, keefektifan. Jenis penelitian kuantitatif model (R&D) Borg and Gall. Teknik pengumpulan data: pengamatan, angket, dan tes. Teknik analisis data: validitas dan reliabilitas, aktivitas siswa, keterlaksanaan RPP dan tes berpikir kritis. Hasil validator media Ensiklopedia valid untuk digunakan, diuji di SDN MOJO VI/225 dengan One Group Pretest-Postest Design. Hasil validasi media Ensiklopedia >96% valid, keterlaksanaan RPP >94% terlaksana baik dengan model Discovery Learning, keefektifan tes berpikir kritis N-Gain 0,75 (tinggi), respon positif 97%. Kesimpulan media Ensiklopedia Bentuk dan Fungsi Tumbuhan layak digunakan melatihkan berpikir Kritis.